Characterization of Activated Carbon from Mangosteen Peel (Garcinia Mangostana L.) Activated with Phosphoric Acid (H3PO4) - Indrastika, Erwin Riski; Hidayati, Nasrul Rofiah; Trisnawati, Ade (Universitas Pendidikan Mandalika, 2025)
Mangosteen peel (Garcinia Mangostana L.) represents a waste that has yet to find widespread application. One effort to increase the economic value of mangosteen rind is by processing mangosteen rind into active carbon, which can be used in various industrial processes. This research will examine the manufacture of activated carbon using mangosteen peel as raw material, which is washed clean, cut, and dried, then carbonized using a furnace at a temperature of 250 0C for 1 hour. Activating activated carbon from mangosteen peel is carried out by immersion in a 5 M concentration of phosphoric acid (Hâ‚ƒPOâ‚„). Next, the characteristics of activated carbon from mangosteen peel are examined, including water content, ash content, volatile matter content, and pure carbon content. The study shows that activated carbon meets the SNI-06-3730-1995 standards for its water content (2.76%), ash content (7.24%), volatile matter content (6.02%), and pure carbon content (83.98%).